Para além das métricas: produção científica de docentes no contexto de dois programas de pós-graduação da UTFPR e questões de gênero - Ferreira, Michel Alves (2017)
This dissertation aims to discuss and map the volume of scientific production of teachers in two post-graduate programs in the Campus of Curitiba at the Technological Federal University of Paraná, from three elements: representation of men and women teachers in each program, volume of orientations and co-orientation produced in a timeline of fourteen years and the volume of publications produced between men and women teachers of each program in the last five years. The questioning of these raised data and information had as grounds gender perspective, science and technology, which allowed the comparison of the programs selected for the survey. It is important to highlight that the first category of this research is quantitative and interpretive. It is also pointed out that the databases (Sucupira Platform, Capes Portals, Lattes Platform and sites of programs), as well as the info/bibliometrics, took part in the composition of the quantitative aspects of the research. It was observed that in many cases, the productivity of women teachers was higher in relation to men teachers, and this information could only be obtained when the average of orientations/publications of teachers by sex was considered, rather than just absolute numbers of analyses shown in official bases. It is expected that the survey will motivate institutional actions for the deconstruction of gender/sex stereotypes, as well as the promotion of future research on gender relations, visibility of production of women teachers and the academic institutions, since this issue is not imperious.